2005
DOI: 10.1080/13557850500096878
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Mental Disorders in Second-Generation Immigrants in Sweden: A Four-Year Cohort Study

Abstract: Many groups of second-generation immigrants have a higher risk of being hospitalised for mental disorder than the majority population. With increasing global migration it is crucial for all industrialised countries to take measures to improve mental health among second-generation immigrants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 31 publications
2
32
0
Order By: Relevance
“…Several studies reported different rates between first generation and second generation immigrants with regard to several health issues, e.g. suicide, schizophrenia and coronary heart diseases (151)(152)(153). We could now also show these associations for DP.…”
Section: Study I and Ii: Risk Of Disability Pension In The General Posupporting
confidence: 71%
“…Several studies reported different rates between first generation and second generation immigrants with regard to several health issues, e.g. suicide, schizophrenia and coronary heart diseases (151)(152)(153). We could now also show these associations for DP.…”
Section: Study I and Ii: Risk Of Disability Pension In The General Posupporting
confidence: 71%
“…showing, perhaps, an increased risk of mental disorders, self-harm-and suicidal behaviour as has been shown in earlier studies of second-generation immigrant adults (30)(31)(32)(33). An important factor to keep in mind in all epidemiological studies, and especially when evaluating scores of mental health among individuals with different immigrant backgrounds is that different kinds of expectations and cultural values might have an impact on the way they score (33).…”
Section: Discussionmentioning
confidence: 99%
“…Increased risk for a broader range of psychiatric disorders associated with mixed parentage has been found previously in a Swedish study. 34 Although the presence of a Danish parent in the household might lead to greater acceptance of treatment-seeking behavior per se, it is also possible that the selection of a non-Danish mate by a native Dane represents some aspect of vulnerability for psychiatric disorder that could lead to a broader range of psychiatric outcomes in the offspring. Furthermore, although common psychiatric disorders, such as depression, have been found to be associated with socioeconomic adversity, 35 it is unlikely that families with mixed parentage would necessarily have poorer socioeconomic circumstances than families in which both parents are foreign born.…”
Section: Main Findingsmentioning
confidence: 99%